2021
DOI: 10.18510/ijsrtm.2021.933
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Relative Importance of Resilience Indicators for Large-Scale Hospital Buildings to Withstand Hydrological Disasters

Abstract: Purpose of the study: Uninterrupted hospital services and medical functions are the keys to functional resilience to cope with mass casualties. This paper presents the important level of resilience indicators for hospital functions to withstand natural disasters. Methodology: For the survey, 21 indicators are grouped into three domains focusing on i) general concerns of healthcare infrastructure planning ii) design and planning of hospital buildings iii) emergency service and management. The correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…With regards to evaluating capacities, the adaptive capacity is most frequently referenced in the literature on hospital resilience (21, 29,34,36,38,43,48,50,77,78). This may be due to the wide encompassing definitions and variation of "adaptivity" [e.g., "flexibility" (8,18,35,47,48,50,62), "agility" (38, 44), and "performance variability" (13)] and its measures. Studying the wider literature on health systems resilience, a systematic review found the highest number of indicators across different levels of data collection was for the "absorption" domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With regards to evaluating capacities, the adaptive capacity is most frequently referenced in the literature on hospital resilience (21, 29,34,36,38,43,48,50,77,78). This may be due to the wide encompassing definitions and variation of "adaptivity" [e.g., "flexibility" (8,18,35,47,48,50,62), "agility" (38, 44), and "performance variability" (13)] and its measures. Studying the wider literature on health systems resilience, a systematic review found the highest number of indicators across different levels of data collection was for the "absorption" domain.…”
Section: Discussionmentioning
confidence: 99%
“…One study utilized a customized five-dimensional City Resilience Profiling Tool (63), while another evaluated the hospital'sbuilt environment and plans (38) to measure hospital resilience within its environment. Other studies related to natural hazards measured environmental characteristics (e.g., seismic, climaterelated exposures) (10, 40), infrastructural planning and design (47,49,50,63), and modeling to measure hospital's loss of function (39,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations